Revolution Of Animation In Malaysia - Arif Othman (IC-ITECHS, 2020)
Nowadays there is tons variation of animation no matter in form of 2D animation and 3D animation that we can’t even name it. Unfortunately little did we know about origin of animation specifically animation in particular country and region. By using modern searching engine and guidance by association of animation I manage to gather some information that critical and shall be exposed to new generation in the community. For every revolution there must be a spark that ignite the movement of animation in Malaysia. In these case I wonder wheres the starting point of the event and what helping it evolving to the point where are we now. Which I believe it all start when British colonizing Tanah Malaya in 1874. The Malayan Film Unit was created by the British colonialists in 1946 with the intent to produce documentaries and public service announcements of the government and later renamed Filem Negara Malaysia. A set designer working for the Unit named Anandam Xavier was asked to handle an animation project in 1961. Xavier set to work on the first in-country animation short subject